2021
DOI: 10.3389/fimmu.2021.705646
|View full text |Cite
|
Sign up to set email alerts
|

On Deep Landscape Exploration of COVID-19 Patients Cells and Severity Markers

Abstract: COVID-19 is a disease with a spectrum of clinical responses ranging from moderate to critical. To study and control its effects, a large number of researchers are focused on two substantial aims. On the one hand, the discovery of diverse biomarkers to classify and potentially anticipate the disease severity of patients. These biomarkers could serve as a medical criterion to prioritize attention to those patients with higher prone to severe responses. On the other hand, understanding how the immune system orche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 249 publications
(337 reference statements)
1
8
0
Order By: Relevance
“…Intriguingly, cell cycle progression pathways are also enriched in SARS-CoV-2-infected human gastrointestinal cells 33 . In addition to our study, the aforementioned studies confirm that the impact of SARS-CoV-2 on host cell cycle regulation is yet not fully understood 32 and requires further in vivo testing and validation. miRNAs are key players in gene expression regulation through interaction with genes, transcription factors, and other regulatory miRNAs.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Intriguingly, cell cycle progression pathways are also enriched in SARS-CoV-2-infected human gastrointestinal cells 33 . In addition to our study, the aforementioned studies confirm that the impact of SARS-CoV-2 on host cell cycle regulation is yet not fully understood 32 and requires further in vivo testing and validation. miRNAs are key players in gene expression regulation through interaction with genes, transcription factors, and other regulatory miRNAs.…”
Section: Discussionsupporting
confidence: 74%
“…This is further supported by other studies on peripheral blood samples of infected patients in which cell cycle progression was the highest signal among other cellular, metabolic, and signaling pathways [29][30][31] . This may be attributed to the fact that virally infected B cells signal cell cycle progression 32 . Intriguingly, cell cycle progression pathways are also enriched in SARS-CoV-2-infected human gastrointestinal cells 33 .…”
Section: Discussionmentioning
confidence: 99%
“…In our opinion, two factors will contribute to unveil the genetic mechanism that guides the response of macrophages facing the SARS-CoV-2 infection: the high-throughput technologies and the computational/mathematical model of regulatory networks. On one hand, the importance of macrophages in COVID-19 has been evidenced thanks to the transcriptional profiles of thousands of single cells obtained from bronchoalveolar samples in COVID-19-infected patients ( 7 , 20 ). Currently, these massive amounts of data can integrate the gene expression of thousands of genes in thousands of cells from a sample in time and space simultaneously ( 48 ).…”
Section: Future Directions For Macrophages Targeting Agents For Reduc...mentioning
confidence: 99%
“…At this stage, the analysis of these data through machine learning (ML) algorithms can identify how the abundance of macrophages and other immunological cells could be associated with the progression and outcome of the disease. For example, by combining ML algorithms and single-cell RNASeq data from bronchoalveolar samples, we classified COVID-19 patients with different degrees of severity and found that genes associated with a pro-inflammatory response are implicated in severe COVID-19 patients ( 20 ). Besides, it has been reported that unsupervised hierarchical clustering is a proper method to stratify and classify patients through their severity progression determined by the pro-inflammatory, anti-inflammatory, and antiviral cytokines abundance data ( 49 ).…”
Section: Future Directions For Macrophages Targeting Agents For Reduc...mentioning
confidence: 99%
See 1 more Smart Citation